Integrating Brain Gym exercises and progressive muscle relaxation in a college student with neurasthenia: A case report - Kannan, Monisha; Srinivasan, Vignesh; Prathap Suganthirababu; Santhana Lakshmi Sivakumar; Monisha Bakthavatsalam (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Neurasthenia, a condition marked by chronic mental and physical fatigue with poor sleep, is increasingly prevalent among young adults facing academic stress which has been poorly addressed. The case report aims to assess the combined effect of Brain Gym activities and progressive muscle relaxation on fatigue and sleep disturbances in a young adult with neurasthenia in terms of improving mental health outcomes. Case description and management: A 22-year-old male college student presented with persistent fatigue, tension headaches, irritability, and non-restorative sleep for four months. Clinical findings met ICD-10 diagnostic criteria for neurasthenia. Baseline Multidimensional Fatigue Inventory (MFI-20) and Pittsburgh Sleep Quality Index (PSQI) scores were 62 and 10, respectively, indicating severe fatigue and poor sleep. A four-week combined programme of Brain Gym exercises and progressive muscle relaxation was administered five days per week. Post-intervention assessment showed substantial improvement for four weeks, with MFI-20 reduced to 44 and PSQI to 5 signifying better energy levels and improved sleep efficiency. The participant reported high satisfaction, with no adverse events. Conclusion: This case demonstrates that integrating Brain Gym with progressive muscle relaxation may effectively reduce fatigue and enhance sleep quality in college students with neurasthenia, supporting a safe and accessible therapeutic strategy to improve mental health and quality of life.